Localizing English Cartoons: Common Difficulties Regarding Culture Specific References in Audiovisual Translation - Kapezova, G. (MAQSUT NARIKBAYEV UNIVERSITY School of Liberal Arts. Astana, 2025)
In the modern era, audiovisual translation has become increasingly relevant, particularly in relation to the spread of language through films and animated content. Recently, there has been a growing trend of translating foreign films directly into Kazakh. However, the quality of such localizations requires careful analysis. Research in the field of audiovisual translation into Kazakh remains limited. This study aims to examine the localization of the animated film Cars 2, with a specific focus on the translation of culture specific references. A qualitative content analysis is employed to identify the strategies used in the translation process. The findings indicate that cultural substitution is relatively rare in Kazakh localization. However, this is compensated by frequent use of transcreation and the inclusion of local expressions, which help make the content more relatable to the target audience. The research highlights the importance of striking a balance between fidelity to the source and cultural adaptation. The conclusions drawn from this study may be particularly useful for beginner audiovisual translators, who work with the Kazakh language.
Keywords: audiovisual translation, localization, dubbing, culture, cartoon, transcreation